Excessive Concentration of Agricultural Land by Holdings as A Problem of Land Management in Ukraine - Petro BOROVYK; Volodymyr KYRYLIUK; Serge KOLOTUKHA; Mykola KOROTIEIEV; Oksana KROCHAK (Communications of International Proceedings, 2021)
A number of agricultural holdings, which are registered as business entities and taxpayers in Ukrainian metropolitan cities, successfully operate in Ukraine. The business practice of such entities indicates that they lease the land of entire regions for the purpose of agricultural production for a significant period and almost in full. The excessive concentration of land by large agricultural corporations, on the one hand, leads to increased productivity in rural areas, but on the other hand, it leads to the decline of local government budgets, rural social infrastructure and the outflow of urban labor and devastation of villages. The way to solve the problem of agricultural land monopolization is the introduction of special taxes for excessive concentration of agricultural land by the agricultural holdings and for non-compliance with the technology of growing crops.
Keywords: Land Management; Excessive Concentration of Land by Agricultural Holdings; Government Regulation; Tax Regulation